Integrated Urban Drainage Management for Flood Inundation Controlling in Sidokare Area at Sidoarjo Regency - Cahya, Evi Nur; Guntoro, Dani Eko; Harisuseno, Donny (Civil and Environmental Science Journal (CIVENSE), 2019)
Flood and inundation had become a serious problem in Sidoarjo Regency annually. This study aimed to apply integrated urban drainage management for flood inundation controlling at Sidokare Region in Sidoarjo Regency. This integrated drainage management consisted of retarding pond, drainage channel redesign, and pump utilization. The study region was divided into Sidokare Pump station, Sepande, and Diponegoro Street catchment area. Rainfall intensity during historical floods was analysed using Mononobe formula and Log Pearson Type III method was used to analyze design rainfall. From the result of the analysis, it wasfoundthat thehistoricalfloodsinstudyregioncausedbyrainfall withreturnperiodof1.01 years, with rainfall intensity of 17.55 mm/hour. It was also found that by implementing this integratedurbandrainagemanagementatSidokareRegion,floodcouldbereducedupto100%. ForSidokarePumpStationcatchmentarea,theinundationmanagementwasconductedbyusing combination of storage pool, existing drainage channel, and the existing flood pump. For Sepandecatchmentarea,itwasmanagedtousethecombinationofstoragepoolandtheexisting drainage channel. Meanwhile, Diponegoro Street catchment area was solved by utilizing new flood pump combining with new tertiary channel and existing drainagechannel.